Effect of hydroxyurea treatment on renal function parameters: Results from the multi-center placebo-controlled BABY HUG clinical trial for infants with sickle cell anemia - Alvarez, Ofelia; Miller, Scott T.; Wang, Winfred C.; Luo, Zhaoyu; McCarville, M. Beth; Schwartz, George J.; Thompson, Bruce; Howard, Thomas; Iyer, Rathi V.; Rana, Sohail R.; Rogers, Zora R.; Sarnaik, Sharada A.; et al. (Pediatric blood & cancer, 2012)
Background Children with sickle cell anemia (SCA) often develop hyposthenuria and renal hyperfiltration at an early age, possibly contributing to the glomerular injury and renal insufficiency commonly seen later in life. The Phase III randomized double‐blinded Clinical Trial of Hydroxyurea in Infants with SCA (BABY HUG) tested the hypothesis that hydroxyurea can prevent kidney dysfunction by reducing hyperfiltration. Procedure 193 infants with SCA (mean age 13.8 months) received hydroxyurea 20 mg/kg/day or placebo for 24 months. 99mTc diethylenetriaminepentaacetic acid (DTPA) clearance, serum creatinine, serum cystatin C, urinalysis, serum and urine osmolality after parent‐supervised fluid deprivation, and renal ultrasonography were obtained at baseline and at exit to measure treatment effects on renal function. Results At exit children treated with hydroxyurea had significantly higher urine osmolality (mean 495 mOsm/kg H2O compared to 452 in the placebo group, P = 0.007) and a larger percentage of subjects taking hydroxyurea achieved urine osmolality >500 mOsm/kg H2O. Moreover, children treated with hydroxyurea had smaller renal volumes (P = 0.007). DTPA‐derived glomerular filtration rate (GFR) was not significantly different between the two treatment groups, but was significantly higher than published norms. GFR estimated by the Chronic Kidney Disease in Children (CKiD) Schwartz formula was the best non‐invasive method to estimate GFR in these children, as it was the closest to the DTPA‐derived GFR. Conclusion Treatment with hydroxyurea for 24 months did not influence GFR in young children with SCA. However, hydroxyurea was associated with better urine concentrating ability and less renal enlargement, suggesting some benefit to renal function. (ClinicalTrials.gov number NCT00006400) Pediatr Blood Cancer 2012;59:668–674. © 2012 Wiley Periodicals, Inc.